Tracing the Trajectory and Development of Language Teachers’ Resilience Stories from the Saudi context - Aloufey, Mariam (2024)
Across the world, teachers in general and language teachers in particular, are experiencing significant levels of stress and burnout, leading to their exodus from the profession. The construct of resilience gained considerable interest in education, and studies on resilience have been rapidly growing as it provides a comprehensive framework on how resilient teachers maintain their motivation and commitment to the profession. Although teacher resilience has been widely research in Western contexts, to date no research has examined language teacher resilience in the Saudi context. Accordingly, three qualitative studies have been conducted in sequence to examine the development and trajectories of Saudi language teachers’ resilience throughout their career span. The first of these was an exploratory study that aimed to examine the teaching challenges that teachers experienced throughout the years and how they coped. Data from 11 teachers revealed universal and specific teaching challenges to the Saudi context, and use of faith as one of their coping strategies. Significantly, the data suggested four resilience archetypes that were called 1) A smooth resilience 2) roller-coaster resilience, 3) maladaptive resilience, and 4) a reluctant resilience. To further investigate these findings, a second study was conducted with the 4 teachers representing the archetypes. The results revealed that teachers’ resilience developed gradually and emerged from the dynamic interaction between teachers’ inner systems, which included many components (e.g., learning experience, and self-efficacy) and the different contextual factors in the teaching context over time. Furthermore, the study showed the complex change and development of coping strategies influenced by the reciprocal interaction between teachers and their contexts. The final study used focus groups interviews (N=13) to examine the relevance of the resilience archetypes and continuing professional development programmes as tool to develop and maintain teacher resilience. Findings suggest that the rollercoaster archetype was most experienced by teachers (N=6), followed in order by smooth archetype (N=4), reluctant archetype (N=2) and maladaptive archetype (N=1). Furthermore, study revealed limited access to formal CPD opportunities and teachers’ engagement with self-directed CPD to overcome teaching challenges. The research conclusion suggests future research and include teacher’s recommendations for CPD that help promote their resilience .